Hemolytic Uremic Syndrome: New Developments in Pathogenesis and Treatment - Olivia Boyer; Patrick Niaudet (International Journal of Nephrology)
Hemolytic uremic syndrome is defined by the characteristic triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. In children, most cases of HUS are caused by Shiga-toxin-producing bacteria, especially Escherichia coli O157:H7. Common vehicles of transmission include ground beef, unpasteurized milk, and municipal or swimming water. Shiga-toxin-associated HUS is a main cause of acute renal failure in young children. Management remains supportive as there is at present no specific therapy to ameliorate the prognosis. Immediate outcome is most often favourable but long-term renal sequelae are frequent due to nephron loss. Atypical HUS represents 5% of cases. In the past 15 years, mutations in complement regulators of the alternative pathway have been identified in almost 60% of cases, leading to excessive complement activation. The disease has a relapsing course and more than half of the patients either die or progress to end-stage renal failure. Recurrence after renal transplantation is frequent.